A miniaturized electrothermal array for rapid analysis of temperature preference behaviors in ecology and ecotoxicology. (1st December 2022) - Henry, Jason; Bai, Yutao; Kreuder, Florian; Saaristo, Minna; Kaslin, Jan; Wlodkowic, Donald
Abstract: Due to technical limitations, there have been minimal studies performed on thermal preferences and thermotactic behaviors of aquatic ectotherm species commonly used in ecotoxicity testing. In this work, we demonstrate an innovative, purpose-built and miniaturized electrothermal array for rapid thermal preference behavioral tests. We applied the novel platform to define thermal preferences in multiple invertebrate and vertebrate species. Specifically, Dugesia notogaea (freshwater planarians), Chironomus tepperi (nonbiting midge larvae), Ostracoda (seed shrimp), Artemia franciscana (brine shrimp), Daphnia carinata (water flea), Austrochiltonia subtenuis (freshwater amphipod), Physa acuta (freshwater snail), Potamopyrgus antipodarum (New Zealand mud snail) and larval stage of Danio rerio (zebrafish) were tested. The Australian freshwater water fleas, amphipods, snail Physa acuta as well as zebrafish exhibited the most consistent preference to cool zones and clear avoidance of zones >27 °C out of nine species tested. Our results indicate the larval stage of zebrafish as the most responsive species highly suitable for prospective development of multidimensional behavioral test batteries. We also showcase preliminary data that environmentally relevant concentrations of pharmaceutical pollutants such as non-steroidal anti-inflammatory drug (NSAID) ibuprofen (9800 ng/L) and insecticide imidacloprid (4600 ng/L) but not anti-depressant venlafaxine (2200 ng/L) and (iv) anticonvulsant medications gabapentin (400 ng/L) can perturb thermal preference behavior of larval zebrafish. Collectively our results demonstrate the utility of simple and inexpensive thermoelectric technology in rapid exploration of thermal preference in diverse species of aquatic animals. We postulate that more broadly such technologies can also have added value in ecotoxicity testing of emerging contaminants. Graphical abstract: Image 1 Highlights: Behavior-modifying pharmaceutical micropollutants are an increasing global risk. Impact of pollutants on thermal preference behaviors is greatly understudied. Miniaturized Peltier technology allows rapid analysis of thermotactic behaviors. New technique reveled zebrafish as suitable for thermotactic biotests. Ibuprofen and imidacloprid perturb zebrafish thermal preference behavior.